Avaliação do processo de implantação da estratégia de saúde da família : o caso de Resistência - Cruz, Sheila Cristina de Souza (2007)
This study is restricted to the health assessment field, having as reference the Social Sciences‟ view of this field. This study aims at the implantation of the Family Health Strategy (ESF) in Resistência, São Pedro area, City of Vitória/ES. The investigation intended to map out the innovative possibilities of organization of assistance practices, as well as study the contributions of the ESF implantation to the served communities. Both official documents and relevant studies were analyzed. The methodological approach chosen was qualitative, through case study. Data were obtained between February and April of 2006, through field observation and interviews using semi-structured forms and with users registered in the ESF and health professionals involved in this community‟s assistance. The obtained results were analyzed through the Collective Subject Discourse (CSD) technique, which showed, in general terms, both the users‟ satisfaction with the service at the Family Health Unit (USF), and the increased access of these users to health services. However, the results also showed the need of revising the teams‟ assistance practices. It was made evident that the basic assistance activities are centered in the USF and that the work organization still focuses on individual health assistance, which reduces service response to the demand. Users also showed to be unaware of both the family health team's actions and the ESF directives by the health professionals. It was also clear that labor turnover unbalances the teams and encourages the repetition of emergency service practices at the USF. The questions raised by this study indicate the need of broadening listening, qualifying bonds and seeking local innovations with more community interaction. Results pointed out that health professionals see the need of changing their practice and the way to promote good health. However, their limitations due to the life style of the families make these professionals suffer from not being able to solve problems beyond their competence. From these findings, it was concluded that it is necessary to adapt the strategy practice to the theory offered by the Ministry of Health in order to improve service quality. The results of this study can contribute to ESF adaptations concerning assistance or managerial innovations aiming at improving the work process.